Alexander the Great, the royal throne and the funerary thrones of Macedonia - Olga Palagia (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2018)
There is no evidence in either Greece or Macedon in the archaic and classical periods that the throne functioned as a symbol of royalty. Thrones were for the gods and their priests. Only the king of Persia used a royal throne and even had portable thrones for his campaigns. This paper argues that after his conquest of the Persian Empire, Alexander the Great adopted the throne as a royal symbol; after his death, his throne became a token of his invisible presence. Philip III Arrhidaeus is known to have used a royal throne after his return to Macedonia. By implication, the marble thrones found in three tombs at Vegina–Aegae are here understood as symbols of royalty and the tombs are interpreted as royal.